2012
DOI: 10.1063/1.3695369
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of energy in the Ding-Dong model

Abstract: We study the properties of energy spreading in a lattice of elastically colliding harmonic oscillators (Ding-Dong model). We demonstrate that in the regular lattice the spreading from a localized initial state is mediated by compactons and chaotic breathers. In a disordered lattice, the compactons do not exist, and the spreading eventually stops, resulting in a finite configuration with a few chaotic spots.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…We have found that with the FNDE it is possible to explain in a consistent way the subdiffusive spreading behavior and the energy scaling of spreading states. Analysis of self-similar solutions of the FNDE not only predicts a subdiffusive spreading, but also induces a scaling of time and energy of the spreading process according to relations (21) and (22), which depend on parameters γ and a, responsible for the index of the fractional time derivative and of the nonlinearity, respectively. We tested these scaling laws on a class of nonlinearly coupled oscillators with different values of the nonlinear indices κ (local nonlinearity) and λ (coupling nonlinearity).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have found that with the FNDE it is possible to explain in a consistent way the subdiffusive spreading behavior and the energy scaling of spreading states. Analysis of self-similar solutions of the FNDE not only predicts a subdiffusive spreading, but also induces a scaling of time and energy of the spreading process according to relations (21) and (22), which depend on parameters γ and a, responsible for the index of the fractional time derivative and of the nonlinearity, respectively. We tested these scaling laws on a class of nonlinearly coupled oscillators with different values of the nonlinear indices κ (local nonlinearity) and λ (coupling nonlinearity).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the strongly nonlinear lattices studied here have only a nearestneighbor coupling without a random coupling coefficient. Similarly to the studies before, we analyze the excitation times T (L) as a function of excitation length L for different energies E to check the predictions of the FNDE scaling (22). At first, we report the results for κ = 2 and λ = 4.…”
Section: Harmonic Oscillators Nonlinear Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…This is done by Gaspard and Gilbert, 21 who analyze the energy transfer processes of interacting hard spheres. Energy spreading is discussed in the work of Roy and Pikovsky 22 in the regular lattice of the Ding-Dong model. It is natural to ask if billiard particles can acquire unlimited energy when colliding with a moving boundary.…”
mentioning
confidence: 99%